Genome-wide identification and characterization of eukaryotic protein kinases - Kanhu Charan Das; Parismita Kalita; Timir Tripathi (Frontiers in Bioscience-Landmark, 2020)
The tropical liver fluke, Fasciola gigantica is a food-borne parasite responsible for the hepatobiliary disease fascioliasis. The recent completion of F. gigantica genome sequencing by our group has provided a platform for the systematic analysis of the parasite genome. Eukaryotic protein kinases (ePKs) are regulators of cellular phosphorylation. In the present study, we used various computational and bioinformatics tools to extensively analyse the ePKs in F. gigantica (FgePKs) genome. A total of 455 ePKs were identified that represent ~2% of the parasite genome. Out of these, 214 ePKs are typical kinases (Ser/Thr- and Tyr-specific ePKs), and 241 were other kinases. Several FgePKs were found to possess unusual domain architectures, which suggests the diverse nature of the proteins that can be exploited for designing novel inhibitors. 115 kinases showed <35% query coverage when compared to human ePKs highlighting significant divergences in their respective kinomes, further providing a platform for novel structure-based drug designing. This study provides a platform that may open new avenues into our understanding of helminth biochemistry and drug discovery.